Pembelajaran Discovey dan Powtoon dalam Menulis Teks Recount: Respon dan Tantangan Siswa - Siska Rizkiani; Angga Maulana; Setya Resmini (English Education Department of STKIP Pasundan, 2023)
This study investigates students' responses to utilizing discovery learning using PowToon for writing recount texts. The students' responses include four variables from Muhlisin (2018): attention, relevance, confidence, and satisfaction. Moreover, the challenges encountered by students are also examined. This research utilizes a descriptive qualitative approach. This research focuses on tenth-grade students from a vocational high school in Cimahi. Data is gathered through questionnaires, tests, and interviews. The findings indicated that the research was well-received by the students. The methodology and instructional materials facilitated the student's comprehension of the course, leading to increased motivation in producing a well-written recount text. The integration of PowToon in teaching recount text had a favorable response from the students. They continued to have difficulties in grammar and vocabulary, as indicated by the low scores on the test results. The assessment labels most students' writing exam results as good or high percentages. The study determined that students comprehend the topic effectively using the discovery learning approach and PowToon. Keywords: challenge; discovery learning; recount text, response; writing